1989
DOI: 10.1128/jvi.63.2.892-900.1989
|View full text |Cite
|
Sign up to set email alerts
|

Addition of high-mannose sugars must precede disulfide bond formation for proper folding of Sendai virus glycoproteins

Abstract: The role of glycosylation and of disulfide bonds in the formnation of the native structure of the Sendai virus hemagglutinin-neuraminidase (HN) and fusion (FO) glycoproteins was studied. In contrast to the HN and Fo synthesized in vivo, the proteins made from pSP6 transcripts in reticulocyte lysates, whether glycosylated or not, were not recognized by monoclonal antibodies or polyclonal rabbit sera raised against the native proteins; they efficiently reacted only with rabbit antisera raised against the reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
21
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 42 publications
7
21
0
Order By: Relevance
“…6). These latter observations are in agreement with previous experiments involving the HN protein of Sendal virus, in which the acquisition of immunoreactivity with conformation-dependent antibodies was dependent upon glycosylation and the formation of correct intramolecular disulfide bonds (38). Under nonreducing conditions, the d140 and d144 proteins migrated as discrete species of increased electrophoretic mobility ( Fig.…”
Section: The D140 and D144 Proteins Form Authentic Intramolecular Dissupporting
confidence: 92%
“…6). These latter observations are in agreement with previous experiments involving the HN protein of Sendal virus, in which the acquisition of immunoreactivity with conformation-dependent antibodies was dependent upon glycosylation and the formation of correct intramolecular disulfide bonds (38). Under nonreducing conditions, the d140 and d144 proteins migrated as discrete species of increased electrophoretic mobility ( Fig.…”
Section: The D140 and D144 Proteins Form Authentic Intramolecular Dissupporting
confidence: 92%
“…We have previously shown that GSH inhibits replication of parainfluenza-1, herpes simplex-1, and HIV-1 viruses by a direct effect on the envelope glycoproteins (17,31,32). One of the characteristics shared by these proteins is that their assembly into oligomers depends on the formation of disulfide bonds, which are strongly affected by reducing agents such as GSH (66,67). The influenza A virus glycoprotein HA is organized as a homotrimer, and each monomer consists of two disulfide-linked subunits, HA1 and HA2 (54).…”
Section: Discussionmentioning
confidence: 99%
“…This was unexpected because most proteins are glycosylated co-translationally during entry into the ER (2,5,25). Since the folding of some proteins and their transportation from the ER can be greatly affected by glycosylation (24,31), we considered the possibility that the observations made with VP7 might be connected with the mechanism by which this protein is retained in the ER. In this work, we examine the kinetics of VP7 glycosylation in more detail and investigate the reason for its delay.…”
mentioning
confidence: 99%